PENGARUH PEMAHAMAN SURAH AL-INSYIRAH AYAT 5-6 TERHADAP POLA PIKIR MAHASISWI ILMU AL-QUR’AN DAN TAFSIR DI INSTITUT AGAMA ISLAM IMAM SYAFI’I INDONESIA - Mutiya Syahrial; Mochammad Novendri Saputra; Syafi'i Syafi'i (STAI Asy-Syukriyyah, 2026)
Mindset plays an important role in shaping how students understand, evaluate, and respond to academic and life challenges. Surah Al-Insyirah verses 5–6 contain values of optimism and mental reinforcement through the teaching that every hardship is always accompanied by ease. Previous studies have examined the relevance of Surah Al-Insyirah to psychological aspects such as academic stress and self-efficacy, yet quantitative studies specifically testing the relationship between understanding of this verse and students' mindset remain scarce. This study aims to determine the relationship between understanding of Surah Al-Insyirah verses 5–6 (X) and the mindset of female students (Y) of the Qur'anic Studies and Tafsir Program at Institut Agama Islam Imam Asy-Syafi'i Indonesia. This study employed a quantitative approach using proportionate stratified random sampling. The initial sample consisted of 106 respondents (Slovin formula); however, after data screening to remove incomplete, inconsistent, and outlier responses, the final sample used for analysis was 84 respondents (N = 84). Data were collected through a 1–5 Likert-scale questionnaire. Validity testing showed all items were valid (r calculated > r table of 0.212), and reliability testing showed the instrument was reliable (Cronbach's Alpha of 0.834 and 0.795). Descriptive statistics showed both variables were in the high category (mean X = 4.30; mean Y = 4.33). The Kolmogorov-Smirnov normality test showed the data were not normally distributed (Sig. = 0.001), so the hypothesis was tested using Spearman's Rho. The correlation result showed a coefficient of -0.029 with a significance of 0.794 (> 0.05), leading to acceptance of H0. It is concluded that there is no significant relationship between understanding of Surah Al-Insyirah verses 5–6 and students' mindset, with a very weak and negative relationship strength, indicating that cognitive understanding alone is insufficient to shape mindset without a process of value internalization.